Looking beyond the powder/dense flow avalanche dichotomy - Faug, T.; Turnbull, Barbara; Gauer, P. (American Geophysical Union, 2018)
Köhler et al. (2018) deploy a high spatial and temporal resolution GEODAR radar system to reveal the inside of snow avalanches over the entire slope. They detect a rich variety of longitudinal and slope normal flow structures across a data set of 77 avalanches recorded over 6 years. Distinctive features in the radar signatures permit the definition of seven flow regimes and three distinct stopping signatures, illustrating behaviours much richer than the conventional dichotomy between dense flow avalanches and powder snow avalanches. This presents modellers with the challenge of exploring the physics of these regimes, the transitions between them and their relationship with the surrounding conditions.